Pengaruh Pembelajaran Kooperatif, Komunikasi Interpersonal dan Aktifitas KKG Terhadap Prestasi Belajar Sejarah Kebudayaan Islam pada Siswa Kelas V MI Al Muhsinun Kauman dan MI An Nahdiyah Gedeg - Hasan H.A. Buro (PROGRESSA: Journal of Islamic Religious Instruction, 2017)
Model Cooperative Learning is a learning model which was used as an alternative to delivering innovation learning outcomes. This model has several advantages, which enable students to succeed in learning, skills training, leading the Active Interaction Between Students and teachers learning atmosphere relaxed and fun. the purpose of the study is 1) Describe the effects of cooperative learning in the Islamic Cultural History on student learning achievement. 2) Describe the effect of interpersonal communication in the history of Islamic culture on student learning achievement. 3) Describe the effect of KKG for student achievement Cultural History of Islam in students. 4) Describe the effects of cooperative learning, interpersonal communication and KKG for student achievement Cultural History of Islam in students. From the analysis can be summarized as follows: 1) There is an effect of cooperative learning on the learning achievement of Islamic Cultural History. in MI Al Muhsinun kauman regression coefficient (B) 0.417, with a significance t is 0, .001 Because of the significance of t less than 5% (0001, <0.05) and MI An Nahdiyah Gedeg regression coefficient (B) 0523, with significance of 0,005 t. Because of the importance of not less than 5% (0.005 <0.05), 2) There is an effect of interpersonal communication on the learning achievement of Islamic Cultural History. in class V MI Al Muhsinun kauman regression coefficient (B) 0050, with a significance of 0.004 t. Because of the importance of not less than 5% (0.004 <0.05) and Class V MI An Nahdiyah Gedeg regression coefficient (B) 0.322, with a significance of 0.046 t. Because of the importance of not less than 5% (0, <0.05), 3) There is an effect on learning achievement KKG Cultural History of Islam in class V MI Al Muhsinun kauman regression coefficient (B) 0.290, with a significance of 0.000 t. Because of the importance of not less than 5% (0.000 <0.05), and Class V MI An Nahdiyah Gedeg regression coefficient (B) 0.291, with a significance of 0.000 t. Because of the importance of not less than 5% (0, <0.05), the Nil Hypothesis (H0) 4) There is an effect of cooperative learning, interpersonal communication and KKG for student achievement Cultural History of Islam in class MI Al Muhsinun kauman (value obtained Fhitung 2,236 (significance F = 0.000). So F count> F table (2.236> 1.69) or Sig F <5% (0.000 <0.05).) and MI An Nahdiyah Gedeg. (Provided the value of F from 2803 (significance F = 0.000). So F count> F table (7158.057> 1.69) or Sig F <5% (0.000 <0.05).